Collaborative ethnographies: Reading space to build an affective inventory. (May 2020) - McDuie-Ra, Duncan; Ho, Elaine Lynn-Ee; Jakimow, Tanya; Somaiah, Bittiandra Chand
Abstract: Collaboration in qualitative research is increasingly encouraged and rewarded in many national and global funding schemes. Collaboration by scholars in (radically) different disciplines using different methods is becoming common, however less attention is given to collaboration using shared approaches across closely-related disciplines. This paper considers the ethnographic insights of four researchers from different (but related) disciplinary backgrounds who conducted collaborative fieldwork in one site—West Coast Park (WCP) in Singapore—over two periods of fieldwork. We conducted an experimental collaboration to study emotions, affect and mundane space through sharing and comparing our interpretations of everyday life in WCP. We ask, how do researchers capture or speak to the affective properties circulated during collaboration? Second, how should researchers approach the affective properties of mundane activities in space? Our paper develops a four-fold 'affective inventory' consisting of: a) multiple-attunements to the (un)familiar; b) attentiveness to affective affordances and their governing effects; c) attentiveness to involuntary affective charges, and; d) awareness of how our diverse affective biographies affect the (im)perceptibility of affect. We propose that such an inventory functions as a valuable guidepost in navigating collaborative ethnographies, especially when exploring emotions and affect. Highlights: Collaborative ethnographic research on emotions, affect and space is challenging. Reading spaces affectively and collaboratively deepens our understanding of nation-building and community-making. Collaborative research on affect and emotions is bolstered by a shared 'affective inventory'. Research on affect and emotions is essential in mundane spaces as well as in spectacular or fraught spaces.